Peningkatan Literasi dan Keterampilan Media Digital melalui Pelatihan Multimedia, Videografi, dan Fotografi di SMK Telkom Makassar - Muh. Ihsan Zulfikar; Zainuddin Zainuddin; Muhammad Riska; Ayu Lestari; Kurnia Wahyu Prima (Universitas Negeri Makassar, 2026)
Abstract. The rapid advancement of digital technology demands that vocational high school students possess adequate digital media literacy and practical skills in multimedia production, videography, and photography. This community service activity aimed to improve the digital literacy and digital media skills of students at SMK Telkom Makassar through structured training covering three main areas: multimedia production, basic videography, and photography techniques. The training was conducted over two days with 35 student participants from the Multimedia program. The method applied was participatory training consisting of lectures, hands-on practice, guided workshops, and mentoring sessions using accessible digital tools including CapCut, Adobe Lightroom Mobile, and basic DSLR/smartphone cameras. Assessment was carried out through pre-test and post-test instruments covering five competency aspects. Results showed that the average score increased from 44.7% (pre-test) to 78.1% (post-test), representing an overall improvement of 33.4 percentage points. The greatest improvement was observed in videography skills (38.2% increased skills in Videography) and digital content production (35.8% increased skills in Digital Content Production). Participants demonstrated increased confidence and practical capability in producing digital media content independently. These findings suggest that structured, practice-based training in digital media skills is effective in building vocational students' readiness for the creative industry. Keywords: digital literacy, photography, videography, multimedia, SMK, community service